ANALISIS PENERAPAN SANKSI ADAT TALA PADA PERKAWINAN ADAT DI DESA RANGGI KECAMATAN WAE RI’I KABUPATEN MANGGARAI - Jemima, Hildegardis; Mauritsius, Darius; Dinata, Husni Kusuma (Petitum Law Journal, 2025)
This study explores the customary tala sanctions applied in traditional Manggarai marriages in Ranggi Village, Manggarai Regency, using an empirical approach through interviews and literature analysis. Tala is a customary fine imposed for the cancellation of a customary marriage that has not been officially registered (either by the state or religion) or for premarital sexual relations. The purpose of tala is to restore women's dignity (molas kole) and end kinship relations (woe nelu) in an honorable manner (pedeng kole roto). The stages in this process consist of: (1) a visit from the woman to the man's family, (2) customary deliberation (lonto leok) to determine the amount of the fine, and (3) submission of sanctions (leso tala) in the form of money (average Rp. 40 million) or animals. Several factors that cause this include neglect of responsibility (for example: rejection of children), communication problems, violation of customary norms, and unpreparedness to start a family. Although this is contrary to the principle of marriage permanence regulated in Law No. 1/1974, tala remains relevant as a form of restorative justice that maintains social balance, women's dignity, and shared responsibility amidst the tide of modernization.